Development of enzymatically produced chitooligosaccharide from shrimp industrial waste: opportunity and challenge - Ekowati Chasanah (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2010)
Since identified having better properties such as solubility in water and bioactivities comparedto its polymer form, chitooligosaccharide has obtained great attention either from researcher andindustries. Wide application of chitooligosaccharides, from pharmaceutical, food and agriculture,is very depending on the deacetylation degree and the size of oligosaccharide. Enzymaticproduction is more dependable in producing specific, safe and environmentally friendlychitooligosaccharide. Chitosanase is one of chitin degrading enzymes group, having importantrole in production of chitooligosaccharide. Shrimp and crustacean waste which are abundant inIndones ia are important raw material for chitin and its deriv ativ e produc ts inc ludingchitooligosacharide and as a source of chitin degrading enzymes including chitosanase. RCMFPPBhas a c ollec tion of potential c hitin degrading mic robes for produc ing func tionalchitooligosaccharides for food, pharmaceutical and biocontrol applications. There is a bigopportunity for Indonesia as chitooligosaccharide producer as we have relatively big amount ofraw material from shrimp and crustacea’s waste, and local enzyme. One of the problem is thelegality of chitooligosaccharide for food and pharmaceutical products has not been available yet.Another non food application such as biocontrol can be developed first since this product does notneed strict regulation as for food.